9. OSTEOPOROSIS AND ASSOCIATED FACTORS IN PATIENTS WITH NON-DIALYSIS CHRONIC KIDNEY DISEASE (Vietnam Journal of Community Medicine, 2025)
Objectives: The study aimed to investigate the relationship between osteoporosis and clinical and paraclinical factors in patients with chronic kidney disease stage 3-5 who have not yet received dialysis.Materials and methods: Descriptive cross-sectional study included 101 patients with chronic kidney disease not receiving renal replacement therapy at the Department of Nephrology and Rheumatology, Hue Central Hospital from April 2021 to June 2023. Bone mineral density was measured using Dual-energy X-ray Absorptionmetry.Results: Bone mineral density decreased with age. Females exhibited lower bone mineral density compared to males and postmenopausal women had lower bone mineral density than premenopausal women. According to WHO standards, osteoporosis in the lumbar spine, femoral neck, total hip and any proportion has respectively 53.5%, 7.9%, 21.8%; osteopenia in the lumbar spine, femoral neck, total hip have proportion of 23.8%, 24.8%, 40.6%, respectively. Osteoporosis in patients with chronic kidney disease based on bone mineral density cut off value of 0.625 g/cm2 in the lumbar spine, femoral neck, total hip have proportion of 19.8%, 30.7%, 29.7%, respectively. Bone mineral density at 3 measurement locations had a negative correlation with age. Bone mineral density of the lumbar spine had a positive correlation with the BMI (r = 0.206). The bone mineral density of lumbar spine L1-L4 had a negative correlation with abdominal aortic calcification score calculated on the Kauppila scale (p < 0.001). Bone mineral density of the total hip had a negative correlation with phosphorus (r = -0.209), calcium × phospho (r = -0.242), PTH (r = -0.231).Conclusion: The prevalence of osteoporosis and osteopenia in patients with chronic kidney disease was high. Bone mineral density had a negative correlation with age. Bone mineral density of the lumbar spine had a positive correlation with BMI and a negative correlation with abdominal aortic calcification score. Bone mineral density of the total hip had a negative correlation with phosphorus, calcium × phospho, PTH.
Keywords: Chronic kidney disease; bone mineral density; osteoporosis.